2020
DOI: 10.1002/cam4.3114
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and predictors of lymph nodes metastasis and distant metastasis in newly diagnosed T1 colorectal cancer

Abstract: Background Lymph nodes metastasis (LNM) and distant metastasis (DM) are important prognostic factors in colorectal cancer (CRC) and determine the following treatment approaches. We aimed to find clinicopathological factors associated with LNM and DM, and analyze the prognosis of CRC patients with T1 stage. Methods A total of 17 516 eligible patients with T1 CRC were retrospectively enrolled in the study based on the Surveillance, Epidemiology, and End Results (SEER) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Nomograms can also present simple statistical analysis and visualization results, which are helpful for clinical decisionmaking and for promoting the development of personalized medical therapy. Recently, nomograms have been broadly applied to predict the risk of LNM in different tumors and have been proven to be effective (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms can also present simple statistical analysis and visualization results, which are helpful for clinical decisionmaking and for promoting the development of personalized medical therapy. Recently, nomograms have been broadly applied to predict the risk of LNM in different tumors and have been proven to be effective (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…External validation was exhibited by calibration curves using the validation set. Moreover, we performed decision curve analysis (DCA) 13 to reveal the clinical utility of the nomograms by calculating the net benefits at each threshold probability, while clinical impact curves (CIC) 14 were conducted to help us understand the models’ clinical value more intuitively.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 presents risk factors for LNM from multivariate analyses of studies with more than 400 cases of T1 CRC. 14,[17][18][19][20][21][25][26][27][28] Studies using the same database in the Surveillance, Epidemiology, and End Results (SEER) included one with a longer study period. 19,29 As mentioned in each guideline, lymphovascular invasion (odds ratio [OR], 4.4 to 10.199), histological differentiation (OR, 2.09 to 18.444), tumor budding (OR, 1.70 to 2.350), and depth of submucosal invasion (OR, 2.14 to 5.404) were reported in many studies to be the main risk factors for LNM in T1 CRCs.…”
Section: Curability In the Current Guidelinesmentioning
confidence: 99%
“…They concluded that rectum was a risk factor for LNM (rectum 13.8% vs colon 9.9%: relative risk, 1.4; 95% confidence interval [CI], 1.1 to 1.7; p<0.001). Several studies have divided tumor location into left-and right-sided CRCs, 19,[38][39][40] all of which concluded that left-sided T1 CRCs (10.8% to 12.0%) showed a significantly higher rate of LNM than right-sided tumors (4.8% to 5.4%). Genetic or anatomical features may affect these differences.…”
Section: Additional Risk Factors For Lnmmentioning
confidence: 99%
See 1 more Smart Citation